Rozwiązane

Potęgi!
a)(5-2)² - 3²
b)(√₁₆ - √₂₅) * √4 - 1 =
c) (2½ - 1¼)² - (½)³ =
d)√₁₀₀ - ₆₄ * √25 - √144 =
e)(₁₀₀ - √64 * (³√₁₀₀₀ - ³√₁₂₅) =



Odpowiedź :

a)(5-2)² - 3²=3²-3²=9-9=0
b)(√₁₆ - √₂₅) * √4 - 1 =(4-5)*2-1=(-1)*2-1=-2-1=-3
c) (2½ - 1¼)² - (½)³ =(2²/₄ - 1¹/₄)² -(¹/₈)=(1¹/₄)²-(¹/₈)=(⁵/₄)²-(¹/₈)=(²⁵/₁₆)-(¹/₈)=(²⁵/₁₆)-(²/₁₆)=²³/₁₆=1⁷/₁₆
d)√(₁₀₀ - ₆₄ )* √25 - √144 =√36*√25-√144=6*5-12=30-12=18
e)(₁₀₀ - √64 * (³√₁₀₀₀ - ³√₁₂₅)) =(100-8*(10-5))=100-8*5=100-40=60
lub
(₁₀₀ - √64) * (³√₁₀₀₀ - ³√₁₂₅) =(100-8)*(10-5)=92*5=460
nie wiem gdzie kończy się pierwszy nawias
a)(5-2)² - 3²=3²-3²=0
b)(√₁₆ - √₂₅) * √4 - 1 =(4-5)*2-1=-2-1=-3
c) (2½ - 1¼)² - (½)³ =(1¼)²-⅛=²⁵/₁₆-⅛=²⁵/₁₆ - ²/₁₆=²³/₁₆=1⁷/₁₆
d)√₁₀₀ - ₆₄ * √25 - √144 =10-64*5-12=10-320-12=-322
e)(₁₀₀ - ∛64 * (³√₁₀₀₀ - ³√₁₂₅) =(100-4*(10-5))=100-20=80
a)(5-2)² - 3²=3²-3²=0
b)(√₁₆ - √₂₅) * √4 - 1 =(4-5)*√4 - 1=-1*2-1=-2-1=-3
c) (2½ - 1¼)² - (½)³ =(5/2-5/4)²-(½)³=(10/4)²-(½)³=100/16-1/8=100/16-2/16=98/16=6i⅛
d)√₁₀₀ - ₆₄ * √25 - √144 =10-64*5-12=10-320-12=-310-12=-322
e)(₁₀₀ - √64 * (³√₁₀₀₀ - ³√₁₂₅) =100-8*(10-5)=100-8*5=100-40=60